Inmitten von Providenz und Kontingenz – Tom Tykwers LOLA RENNT - Hohmann, Sophie; Richter, Sarah (Paradigma, 2019)
Tom Tykwers LOLA RENNT (D 1998) brachte der Produktion des deutschen Films internationale Bedeutung. „This resonance was certainly based in part on Lola’s finely tuned – and timely – pop cultural and postmodern sensibilities.“ (Haase 2007: 161)